Ukraine and the Joint Institute for Nuclear Research: Experience and Prospects for Cooperation - Grinyov, B.V.; Volkova, Y.G. (Science and Innovation, 2024)
The article deals with focal points of bilateral cooperation between Ukraine and JINR for the last 20 years. It shows economic and innovative benefit of this collaboration, ways of development and improvement.